IFLA Journal - International Federation of Library Associations (IFLA) (Haugh : International Federation of Library Associations (IFLA), 2015)
IFLA Journal is an international journal publishing peer reviewed articles on library and information services and the social, political and economic issues that impact access to information through libraries. The Journal publishes research, case studies and essays that reflect the broad spectrum of the profession internationally.
Price has decided according to the Guideline for the pricing non-priced periodicals [Rs. 377.00].
Keywords: International librarianship -- Periodicals -- Sri Lanka